Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red. (January 2023) - Mahboob, Iqra; Shafiq, Iqrash; Shafique, Sumeer; Akhter, Parveen; Munir, Mamoona; Saeed, Muhammad; Nazir, Muhammad Shahid; Amjad, Um-e-Salma; Jamil, Farrukh; Ahmad, Nabeel; Park, Young-Kwon; Hussain, Murid
Abstract: Novel Ag3 VO4 /KIT-6 nanocomposite photocatalyst has been successfully fabricated by a newly-designed simple hard-template induction process, in which the particles of Ag3 VO4 were grown on the KIT-6 surface and inside the porous framework of the silica matrix. The developed porous framework nanocomposite was characterized by several techniques including N2 -Physiosorption analysis. The obtained nanocomposite revealed a high surface area (273.86 m 2 /g) along with the possession of monoclinic Ag3 VO4, which is highly responsive to visible light (with distinct intensity at about 700 nm). The UV–Vis DRS reveals that the Ag3 VO4 /KIT-6 photocatalyst bears a bandgap of 2.29 eV which confirms that the material has a good visible light response. The synthesized nanocomposite was tested for its superior physicochemical properties by evaluating its degradation efficiency for Congo Red (CR). The novel composite exhibited superior degradation capability of CR, reaching up to 96.49%, which was around three times the pure Ag3 VO4 . The detailed kinetic study revealed that the as-prepared material followed a pseudo first order kinetic model for the CR degradation. The study includes a comprehensive parametric study for the formulation of the optimized reaction conditions for photocatalytic reactions. The commercial applicability of the composite material was investigated by a regeneration and recyclability test, which revealed extraordinary results. Furthermore, the possible degradation pathway for CR was also proposed. Graphical abstract: Image 1 Highlights: Novel Ag3 VO4 /KIT-6 nanocomposite was successfully synthesized using KIT-6 silica matrix. The nanocomposite exhibited an excellent degradation of Congo Red up to 96.49%. A comprehensive parametric optimization study was successfully carried out. The nanocomposite revealed good commercial applicability during regeneration trials.